PENGARUH PENGETAHUAN WAJIB PAJAK, KESADARAN WAJIB PAJAK, SANKSI PAJAK KENDARAAN BERMOTOR DAN SISTEM SAMSAT DRIVE THRU TERHADAP KEPATUHAN WAJIB PAJAK KENDARAAN BERMOTOR - Anis Syamsu Rizal (Universitas Pamulang, 2019)
This study aims to examine the influence of knowledge of taxpayers, taxpayer awareness, motor vehicle tax sanctions, and samsat drive thru system of tax compliance on motor vehicles in samsat south jakarta. The data that is this study are “primary data from the results of questionnaires. respondents in the system samsat drive thru”. The questionnaire was distributed to 125 respondents and data that can be processed are 100 questionnaires. The sampling method used accidental sampling. The data analysis techniques in this study used “multiple linear regression techniques”.The result of regression analysis shows that “the knowledge of taxpayers, taxpayer awareness and samsat drive thru system have a positive effect on motor vehicle tax compliance while motor vehicle tax sanction has no significant effect on vehicle tax compliance”.